2016
DOI: 10.4103/0976-3147.182777
|View full text |Cite
|
Sign up to set email alerts
|

Deadly intracranial bleed in patients with dengue fever: A series of nine patients and review of literature

Abstract: Introduction:Dengue fever is a global pandemic threat with increasing incidence. To date, there are no cures and the effectiveness of dengue vaccines is still uncertain. World Heath Organization introduced expanded dengue syndrome to include unusual presentations of dengue fever including severe neurologic complications. One of the deadly complications is intracranial hemorrhage (ICH).Methodology:We collected data of patients with ICH diagnosed via a plain computed tomography of the brain (CT brain) with throm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 63 publications
0
16
0
Order By: Relevance
“…Clinical experience from prior studies suggests that patients with secondary dengue infection identified by the detection of IgG early in the course of the disease with a positive NS1 antigen test and negative IgM are at higher risk of ICH carrying poor prognosis and should be monitored more closely with lower thresholds for diagnostic CT of the brain when suspicion of ICH is present. [ 3 ] In the present case report, though the patient was a female without any comorbidities, presence of risk factors of profound shock requiring vasopressor support, seizures, low platelet, and viremia, suggested by positive NS-1 antigen along with altered sensorium prompted early CT scan which revealed suggesting ICH.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Clinical experience from prior studies suggests that patients with secondary dengue infection identified by the detection of IgG early in the course of the disease with a positive NS1 antigen test and negative IgM are at higher risk of ICH carrying poor prognosis and should be monitored more closely with lower thresholds for diagnostic CT of the brain when suspicion of ICH is present. [ 3 ] In the present case report, though the patient was a female without any comorbidities, presence of risk factors of profound shock requiring vasopressor support, seizures, low platelet, and viremia, suggested by positive NS-1 antigen along with altered sensorium prompted early CT scan which revealed suggesting ICH.…”
Section: Discussionmentioning
confidence: 75%
“…ICH, a potential life-threatening complication of dengue, is of uncommon occurrence in patients with severe dengue. [ 3 ] The incidence of dengue encephalopathy is estimated to range from 0.5% to 6.2%. [ 4 5 6 ] However, the incidence of ICH associated with DF is still uncertain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The terminology of 'DF with unusual hemorrhage' was included in the PAHO guidelines in 1994 [20]. More recently, a series of dengue cases presenting with intracranial haemorrhage, but without evidence of severe leakage, were reported by Sam et al [21].…”
Section: Discussionmentioning
confidence: 99%